The Role of ICT in the Smart City Concept - Czupich, Mariusz (Olsztyn Economic Journal, 2019)
The concept of a smart city enables the effective implementation of public services despite the negative consequences related to population growth in large cities. City authorities, in the face of growing demand for public services, often use a wide range of smart city instruments in various areas of operation. Despite the fact that a large part of innovative solutions is widespread and used, such as intelligent transportation systems or e-office, new opportunities are still emerging which are aimed at improving the quality of life for city dwellers. The aim of the article is to define the role of ICT in smart city management. The subjects of analysis are innovative instruments used in technologically advanced cities as well as contemporary challenges facing city management. The functioning of the city depends to a large extent on access to the communication network, mobile devices as well as on infrastructure connected with them. Therefore, it is necessary, on the one hand, to ensure the capacity of connections and network communication, and, on the other hand, to involve citizens in the process of creating new solutions.